(untitled) (Dissertare, 2020)
Teaching and learning processes are often influenced by social changes, driving new theoretical proposals in education and new pedagogical strategies that lead to a redesign of study plans. Socioconstructivism has become a benchmark for these new theoretical proposals and learning strategies. Approaches related to socioconstructivism, such as transformative education, ethnomethodology and the skills approach contain educational approaches that are taken into account in the design of new curricular plans. In this sense, the study plan of the Hellen Keller National Center for Education of Costa Rica (HKNCE), which cares for people with visual disabilities and deafblindness, is designed according to guidelines related to socio-constructivism and the educational approaches mentioned that are associated with same. The purpose of this essay is, first of all, to describe the general aspects of socio-constructivism and its proposal in educational matters, with an emphasis on transformative education approaches, ethnomethodology and the capabilities approach. Secondly, the essay aims to establish the links between socioconstructivism and the aforementioned approaches with the HKNCE study plan in Costa Rica. The work is documentary in nature and relies on critical hermeneutics as an analysis technique. It is concluded that the aforesaid study plan is oriented towards socializing, transformative education, based on humanistic values ​​of social justice, critical thinking and community participation.